2007
DOI: 10.1093/ps/86.8.1633
|View full text |Cite
|
Sign up to set email alerts
|

Molting in Salmonella Enteritidis-Challenged Laying Hens Fed Alfalfa Crumbles. I. Salmonella Enteritidis Colonization and Virulence Gene hilA Response

Abstract: The objectives of this study were to enumerate Salmonella enterica serovar Enteritidis colonization in fecal, cecal, and internal organs, and to compare the level of virulence gene expression (hilA) of experimentally challenged laying hens fed different dietary molt-induction regimens. Twelve Salmonella-free Single Comb Leghorn hens (>50 wk old) hens were randomly assigned to each of 6 treatment groups designated based on diet in 2 trials: 1) feed withdrawal Salmonella Enteritidis-positive (FW+), 2) fully fed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 42 publications
0
23
0
1
Order By: Relevance
“…Increased expression levels of the S. Enteritidis lacZY-hilA fusion gene in cells incubated in crop contents from birds that had undergone feed removal demonstrated that enhanced systemic invasiveness could be linked with increased expression levels of hilA (391). These findings were later replicated and confirmed in vivo by quantitative PCR (392). This increase in S. Enteritidis colonization and invasiveness also coincided with diminished numbers of lactic acid bacteria in the crop and reduced organic acids in the crop (391) and cecum (270,393) and led to major shifts in fecal and cecal bacteria compared to fully fed birds (270,394,395).…”
Section: Salmonella Virulence Response and Competition With Git Micromentioning
confidence: 68%
See 1 more Smart Citation
“…Increased expression levels of the S. Enteritidis lacZY-hilA fusion gene in cells incubated in crop contents from birds that had undergone feed removal demonstrated that enhanced systemic invasiveness could be linked with increased expression levels of hilA (391). These findings were later replicated and confirmed in vivo by quantitative PCR (392). This increase in S. Enteritidis colonization and invasiveness also coincided with diminished numbers of lactic acid bacteria in the crop and reduced organic acids in the crop (391) and cecum (270,393) and led to major shifts in fecal and cecal bacteria compared to fully fed birds (270,394,395).…”
Section: Salmonella Virulence Response and Competition With Git Micromentioning
confidence: 68%
“…Several molt diets with fermentable substrate combinations have been screened in vitro and shown to support optimal avian cecal fermentation (396)(397)(398) and retain similar cecal microbial molecular profiles (397). In vivo application of some of these diets was shown to retain fermentation and GIT populations during molt while limiting the ability of S. Enteritidis to colonize the GIT and become invasive (255,270,392,399,400). The overall results of the studies demonstrate that there is a complex and important relationship between the microflora of the avian GIT and Salmonella, which is key to limiting the pathogen.…”
Section: Salmonella Virulence Response and Competition With Git Micromentioning
confidence: 99%
“…Calcium concentration at the end of moulting was lower in forced-moulted birds than in controls. Dunkley et al (2007) reported similar reductions of calcium in forcedmoulted birds compared with control. Thus, it has been reported that maximising bone mineral deposition before onset of egg production and after moulting is vital to avoid bone weakness problems and improve eggshell qualities in older laying birds (Park et al, 2004).…”
Section: Discussionmentioning
confidence: 65%
“…Also, Donalson et al (2005) reported that using alfalfa in moulting diet resulted in higher Haugh units and lower shell breakage compared with control. Some studies have indicated that moulting affected blood parameters such as glucose, calcium and some hormones (Webster, 2003;Dunkley et al, 2007). The purpose of this study was therefore to investigate the effects of various forced-moulting methods on egg physical and mechanical behaviour, plasma indices and performance in Japanese quails.…”
Section: Introductionmentioning
confidence: 99%
“…McReynolds et al (2006) determined that 100% alfalfa diets as well as diets of 70% alfalfa with 30% standard layer ration reduced colonization of the ceca with S. Enteritidis. Dunkley et al (2007c) orally challenged hens on different molting diets and determined that there was a reduction of colonization by S. Enteritidis when hens were fed 100% alfalfa crumbles as compared to feed withdrawal. There was also an increase in the expression of the hilA gene, a virulence gene of Salmonella in the feed withdrawal group as compared to alfalfa crumbles (Dunkley et al, 2007c).…”
Section: Alternatives To Feed Withdrawal For Moltingmentioning
confidence: 99%